AKTIVITAS OLAHRAGA, JAJAN, DAN UMKM: STUDI WISATA HIBRIDA SERTA IMPLIKASINYA TERHADAP PENGUATAN EKONOMI LOKAL - Aditha Agung Prakoso; Weka Kusumastiti (Jurnal Pariwisata Tawangmangu, 2026)
The phenomenon of recreational physical activity in public spaces is associated not only with health benefits but also with the potential to generate local economic dynamics that remain underexplored within an integrated framework. This study aims to examine the integration of physical activities and micro, small, and medium enterprises (MSMEs) consumption as a form of hybrid tourism practice embedded in everyday life, and its implications for strengthening the local economy. The research was conducted in Tridadi, Sleman, Special Region of Yogyakarta, where active consumption practices accompany high-intensity daily physical activities. A qualitative approach was employed through field observations, in-depth interviews, and documentation. Data were analyzed using descriptive qualitative techniques, including data reduction, categorization, and interpretation. The findings reveal that recreational physical activities catalyze the emergence of temporary informal economic spaces, which contribute to increased MSME transactions, expanded market access, and strengthened social relations between vendors and the community. This integration reflects a fluid and interconnected hybrid tourism practice within everyday spatial contexts. The study highlights that physical activities serve not only as recreational practices but also as mechanisms to strengthen local economic development, offering pathways toward more inclusive and sustainable tourism.